Publicisation et qualité de l'information : la polémique sur la chloroquine - Patrick-Yves Badillo; Laura Puglisi; Dominique Bourgeois (Communiquer)
The coronavirus crisis highlights the importance of the media in publicizing scientific debates. The production and dissemination of reliable information is essential. In this perspective, media ecology appears as a relevant theoretical framework. It is then necessary from a methodological point of view to scrutinize the quality of information. We propose criteria and quantified measures to move in that direction. An application is made on the polemic related to the use of chloroquine, a treatment recommended by Professor Raoult. Our case study covers a period from February 2020 to June 2020. The articles published online by four newspapers of record, either French or Swiss, are analyzed. The results are, undoubtedly, exploratory and should be interpreted with caution. However, we note significant differences between the four media. We also wonder about the major risks of ideologizing scientific debates.